Intramolecular Aldol Ring Closures of Cysteine Derivatives Leading to Densely Functionalised Pyroglutamates - Almahli, Hadia; Jimenez, Niamh C.; Moloney, Mark G. (Synlett, 2019)
The synthesis of densely functionalised pyroglutamates derived from cysteine by an aldol cyclisation strategy has been achieved.
Keywords: aldol reaction; cyclization; heterocycles; pyroglutamate; lactams